OCE-205, a Selective V1a Partial Agonist, Reduces Portal Pressure in Rat Models of Portal Hypertension - Bukofzer S; Harris G; Song S; Cable EE (Dove Medical Press, 2023)
Stan Bukofzer,1 Geoffrey Harris,2 Susan Song,2 Edward E Cable2 1Ocelot Bio, Inc., San Diego, CA, USA; 2Ferring Research Institute Inc., San Diego, CA, USACorrespondence: Stan Bukofzer, Ocelot Bio, Inc., 12670 High Bluff Drive, San Diego, CA, 92130, USA, Tel +1 858-247-2272, Email stan@ocelotbio.comPurpose: Management of decompensated cirrhosis may include the use of vasoconstrictors that can lead to serious adverse events. OCE-205 was designed as a highly selective V1a receptor partial agonist, intended to have a wider therapeutic window than full vasopressin agonists.Methods: We aimed to characterize the activity of OCE-205 treatment in two rat models of portal hypertension (PHT). For both models, OCE-205 was administered as a subcutaneous bolus injection. Thirty male Wistar rats were fed a methionine/choline-deficient (MCD) diet to model PHT. Animals received OCE-205 (10, 25, 100, or 500 μg/kg) or intra-arterial terlipressin (100 μg/kg). In a more severe model of PHT, 11 male Sprague Dawley rats had the common bile duct surgically ligated (BDL) and received OCE-205. Portal pressure (PP) and mean arterial pressure (MAP) were measured.Results: For PP in the MCD model, MAP increased while PP decreased in rats treated with OCE-205 or terlipressin; the peak changes to MAP were 14.7 and 33.5 mmHg, respectively. Changes in MAP began to plateau after 10 min in the OCE-205 groups, whereas in the terlipressin group, MAP rapidly increased and peaked after 20 min. Across all treatment groups in the BDL model, a dose-related decrease from baseline in PP was observed following OCE-205, plateauing as the dose increased. In all treatment groups, PP change remained negative throughout the 30-min testing period. In both PHT rat models, a reduction in PP was coupled to an increase in MAP, with both plateauing in dose-response curves.Conclusion: Data support OCE-205 as a promising candidate for further development.Institutional Protocol Number: Procedures were approved by the Ferring Research Institute (FRI) Institutional Animal Care and Use Committee on July 13, 2011, under protocol FRI-07-0002.Keywords: mean arterial pressure, ascites, HRS-AKI, vasoconstriction, portal hypertension